Effect of low temperature grinding on phytochemicals profile of fenugreek seed powder: Effect of grinding methods on the quality of fenugreek seed powder - Sirwani, Prakash M; Dabhi, Mukesh N; Rathod, Pankaj J (Journal of Spices and Aromatic Crops, 2022)
The grinding of spices at ambient temperature causes the loss of valuable heat-sensitive constituents. While higher investment and maintenance of cryogenic grinding make it prohibitive for small-scale industries. So, the present study was carried out to check the effects of low-temperature grinding on various phytochemicals of ground powder of fenugreek seeds. Water at ambient temperature, chilled water and coolant were circulated around the grinding chamber to lower the grinding temperature. Additionally, fenugreek seeds were fed at ambient and low temperatures (-100C). The temperature inside the grinding chamber at the end of grinding for three kg of fenugreek seeds ranged from 91.330C–53.330C for different treatments. A fall in grinding temperature resulted in the retention of a higher quantity of total phenol (7.71 mg g-1), total flavonoid (12.08 mg quercetin equivalent/g extract), antioxidant activity (21.29%) and volatile components in powder of fenugreek seeds ground by coolant circulation with low-temperature feed.